2017
DOI: 10.1037/ser0000172
|View full text |Cite
|
Sign up to set email alerts
|

University students’ perceived need for mental health services: A study of variables related to not seeking help.

Abstract: This study analyzed data from the 2012 Student Experience in the Research University (SERU) survey, collected from undergraduate students at 9 universities. Researchers explored how demographic and behavioral variables related to avoidance of psychological help when needed. A total of 7,992 SERU participants responded to target items included in the present study. We examined whether student characteristics and behaviors differed between 3 self-report groups: (1) students who indicated they did not need counse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…It is possible that we may have failed to find age-related associations due to the relative homogeneity of our sample with respect to age. Furthermore, while some research has found that women and individuals who identify as White/Caucasian are more likely to seek help Nash et al, 2017), demographic factors interact with each other in more complex ways . Emerging evidence suggests intersectionality (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that we may have failed to find age-related associations due to the relative homogeneity of our sample with respect to age. Furthermore, while some research has found that women and individuals who identify as White/Caucasian are more likely to seek help Nash et al, 2017), demographic factors interact with each other in more complex ways . Emerging evidence suggests intersectionality (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Katz (2005) describes whiteness as maintaining an "everywhere-and-nowhere" position as it maintains its power and normalcy very discreetly despite being embedded in every structure and system within society. For example, the majority of research studies I found focus on the experiences of predominantly white folks in predominantly white institutions dealing with very Eurocentric-based concepts, with the exception of a few authors who discuss the white-settler foundations of education (Andrews & Wilding, 2004;Asher, 2009;Durkee & Williams, 2013;Gillborn, 2005;Hancock, 2001;Hjeltnes et al, 2015;Macaskill, 2013;MacKean, 2011;Martin, 2010;Nash et al, 2017;Rangel, 2016;Reavley & Jorm, 2010;Riviere, 2008;Venville & Street, 2014;Wynaden et al, 2014). Dena Hassouneh (2008) explains that Eurocentrism is entrenched in our educational systems through the standards and traditions held, as well as through the daily practices such as competitiveness and evaluation.…”
Section: Whitenessmentioning
confidence: 99%
“…An additional theme that was common in the existing literature on education is the incidence of mental health concerns among students (Andrews & Wilding, 2004;Durkee & Williams, 2013;Hancock, 2001;Macaskill, 2013;MacKean, 2011;Maclean, 2016;Martin, 2010;Nash et al, 2017;Venville & Street, 2014Vostal, 2015.…”
Section: Mental Health Concernsmentioning
confidence: 99%
“…Poverty also has a great influence on people's mental health (Wu, Tao, Zhang et al, 2015;Kwan, Arbour-Nicitopoulos, Duku et al, 2016;Lesani, Mohammadpoorasl, Javadi et al, 2016;Tao, Wu, Zhang et al, 2017;Poorolajal, Ghaleiha, Darvishi et al, 2017). Some strategies have been proposed to treat mental health problems (Becker, Jarrett, Luebbe et al, 2018;Griggs, 2017;Nash, Sixbey, An, et al, 2017).Domestic research on mental health problems of impoverished college students mainly focuses on the demographic characteristics of psychological problems of impoverished college students, the influencing factors of mental health of impoverished college students, and the solutions to mental health problems of impoverished college students (Hu, 2018). Liu (2017)'s survey on the relationship between parenting style, social support and mental health of poor college students found that compared with the national youth mental health average, the mental health level of poor college students is significantly lower.…”
Section: College Of Economics and Management Hebei University Ofmentioning
confidence: 99%